Clinical and histological features of head and neck melanoma: a population‐based study in France. (11th February 2015) - Dabouz, F.; Barbe, C.; Lesage, C.; Le Clainche, A.; Arnoult, G.; Hibon, E.; Bernard, P.; Grange, F.
Summary: Background: Head and neck melanomas (HNMs) account for an increasing proportion of melanomas and have a poor prognosis. Objectives: To compare the clinical and histological characteristics of HNMs with those of melanomas at other sites (MOS), and to identify pertinent clinicopathological subgroups of HNM. Methods: A retrospective population‐based study of incident in situ and invasive melanomas in the period 2004–2011 was performed. Results: HNMs represented 26·7% of 1548 melanomas, corresponding to a density ratio of 3·7 between HNMs and MOS. HNMs occurred later than MOS (71·2 vs. 58·4 years; P < 0·01), included a higher proportion of in situ cases (49·6% vs. 13·5%; P < 0·01) and were mainly lentigo malignant melanomas (73·0% vs. 2·6%; P < 0·01). Invasive HNMs included a higher proportion of thick (> 2 mm) tumours [33·7% vs. 24·1% ( P = 0·01); mean Breslow thickness: 2·18 vs. 1·77 mm ( P = 0·03)] and nodular melanomas (20·1% vs. 12%; P < 0·01). HNMs in the peripheral area of the head and neck differed from those of central location by a younger age of onset (65·2 vs. 72·4 years; P < 0·01), male predominance (64·4% vs. 33·8%; P < 0·01), and higher proportions of invasive (67·2% vs. 42%; P < 0·01) and nodular (15·1% vs. 7·5%; P = 0·01) melanomas. Conclusions: HNMs highly differ from MOS, and are clinically and histologically heterogeneous, possibly as a consequence of different patterns of sun exposure. These data could help to improve primary and secondary prevention messages for patients and doctors. Abstract : What's already known about this topic? Head and neck melanomas (HNMs) are frequent, occur in elderly people and have a poor prognosis. Population‐based data on HNMs remain limited, and few studies have included a comprehensive comparison with melanomas at other sites (MOS). What does this study add? In this population‐based French study, HNMs differed from MOS by age of occurrence, histological type and a higher proportion of in situ cases, contrasting with a higher proportion of thick tumours. HNMs located in the peripheral and central areas of the head and neck had different clinical and histological features. Different patterns of sun exposure could explain these differences. Specific prevention messages targeting HNMs should be developed.